Engendering Justice : A Gender Assessment's Impact on Project Design - Bhansali, Lisa L. (World Bank, Washington, DC, 2012)
Gender equality is an important indicator of a country's progress toward sustainable development and is one of the Millennium Development Goals. Yet World Bank teams often find gender equality a difficult concept to include in projects. One solution is to conduct a targeted gender assessment, which can help ensure that a project design addresses gender concerns and promotes equitable access to public services.